Deepfakes - When we can no longer believe our eyes and ears: Media manipulation in conflict. Challenges and responses - Aldo Kleemann (Stiftung Wissenschaft und Politik (SWP), 2023)
Deception and media manipulation have always been an integral part of wartime propaganda. But never before has it been so easy to create high-quality fabrications of images as well as sound and video recordings. The tendency to react emotionally to these media opens up a whole new possibility for abuse by their creators. A call to surrender by President Volodymyr Zelensky, which was immediately exposed as a deepfake, is the first attempt to use the new technology in an armed conflict. The quality of such fabrications is improving, detecting them is becoming increasingly complex and there is no end in sight to these developments. Banning deepfakes would be futile. It is therefore time to look at current and potential applications and possible counter-strategies.
Keywords: 320; Deepfake; Fälschung; media manipulation; disinformation; propaganda; hybrid threats; artificial intelligence; Generative Adversarial Network; GAN; generator; discriminator; deep learning; Special Operations Command; Content-Authenticity-Initiative